The Criminal Guardianship as Environmental Instrument Dignity in Law Perspective Iberoamericano - Ribeiro, Luiz Gustavo Gonçalves (2016)
Although it is recognized that the standards of criminal production barn has taken into account, in face of secular dogma, the paradigm of inter-conflicts, demands for protection of diffuse legal interests grow and complain effectiveness. Asked whether, therefore, the environment can and should be in the criminal law field of action, vestibular hypothesis is that that, provided it is of importance to the lives of beings, present and future generations, it is quite legal worthy of dignity that does not derive from individual legal interests, but it has real autonomy and universal and transpersonal. As a matter even survival of criminal law, it should, in the service of society, to interfere in the protection of diffuse legal interest, even with that, have to suffer dogmatic changes in the face of a new criminal policy, as requested by the postmodern society risk. What, however, has been done to the effectiveness of environmental protection will be treated in the work from the perspective of Ibero-American countries, specifically Brazil, Mexico, Argentina, Chile, Colombia and Ecuador, especially in face recognition, before large and recent serious environmental issues, the protection of penal law as a tool for environmental dignity. The issue is of importance for the construction of an international criminal dogmatic for more adequate protection of the environment and will be treated in the deductive methodological perspective. Without prejudice to the literature review contained in books and articles, the text also contains primary data, in due research in newspapers and electronic journals that bring examples of practical application of criminal law for the environment in Ibero-America. The results show that criminal law is applicable to environmental protection.